Vliv temperace a podmínek skladování pryžových dílů na výslednou soudržnost spoje - Jílková, Ingrid (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Tato bakalářská práce se zabývá analýzou výskytu voskových fází na povrchu technické pryže, používané v automobilovém průmyslu. Teoretická část se zabývá rešerší o složení a výrobě pryže. Je zaměřena na složení gumárenské směsi a vosků. Vysvětluje technické vlastnosti, důvody užití a výhody všech přísad gumárenské směsi. Dále objasňuje podstatu vosku a jeho využití v pryži. Dále objasňuje, jak se pryžová pouzdra skladují a také proč je žádoucí vosk na povrchu pryže identifikovat. Praktická část se zabývá návrhem metodiky identifikace vosku na povrchu pryže. Uvádí porovnání metod možností identifikace vosku a jejich vyhodnocení.

This bachelor’s thesis deals with an analysis of waxing phases occurrence on the surface of the technical rubber which is used in the automotive industry. The theoretical part of this thesis deals with a composition and manufacturing of the rubber. It is focused on the composition of rubber compounds and waxes. It explains technical properties, reasons (advantages) of the ingredients in the rubber components. Next, it also clarifies the substance of the wax and its use in relation to rubbers. The theoretical part also clarifies the storage of rubber parts and why is it desirable to identify the wax which is separated on free surfaces of rubber. The practical part deals with a suggestion of the identification methods for the waxes on the surface of rubber. It also presents the comparison of the possibilities of the methods used for the identification of wax and its evaluation.
On the effect of tempering and storage conditions of rubber parts on final joint cohesion
Keywords: pryž; vosk; identifikace; spoj; migrace; rubber; wax; identification; connection; migration